Ab Interno vs. Ab Externo Microcatheter-Assisted Circumferential Trabeculotomy in Treating Patients With Primary Open-Angle Glaucoma - Zhang, Weijia; Wang, Yiwei; Xin, Chen; Sun, Yang; Cao, Kai; Wang, Huaizhou; Wang, Ningli (Frontiers in Medicine, 2021)
Abstract Background: Circumferential trabeculotomy have evolved from ab externo to ab interno approach. Both procedures may lower IOP, but it is unclear which maybe a superior approach. Purpose: To compare the outcomes of ab interno and ab externo circumferential trabeculotomy in patients with primary open-angle glaucoma. Design: Retrospective, comparative case series. Participants: Primary open angle glaucoma patients undergoing ab interno (40 patients in Group 1) or ab externo (54 patients in Group 2) circumferential trabeculotomy, with about one half of them having prior incisional glaucoma surgery. Methods: Outcomes including intraocular pressure (IOP), glaucoma medications and surgical complications were analysed. Main outcome measures: IOP, medications and surgical success defined as an IOP of ≤ 21 mmHg and a reduction of IOP ≥ 20% from baseline (criterion A) or IOP ≤ 18 mmHg and a reduction of IOP ≥ 20% from baseline (criterion B) with (qualified success) or without (complete success) medications. Results：At one year, IOP decreased by 37.1% (26.0 to14.8 mmHg) in Group 1 and 39.5% (28.5 to 15.1mmHg) in Group 2. Medications decreased from 3.5 in Group 1 and 3.6 in Group 2 preoperatively to 0.6 ± 1.0 and 0.3 ± 0.6 postoperatively, respectively. Success rates did not differ significantly between groups based on criterion A (complete and qualified success: 68.7% and 81.9% in Group 1, and 75.3% and 90.4% in Group 2 respectively) or criterion B (complete and qualified success: 58.2% and 79.3%in Group 1, and 69.5%and 88.4% in Group 2 respectively). For eyes with prior filtration surgeries, the mean percent reduction of IOP 41.7% ± 32.7% in Group 1, 39.7% ± 27.8% in Group 2, P = 0.724) and the mean medication reduction (2.9 ± 1.6 in Group 1, 3.4 ± 1.0 in Group 2, P = 0.454) were not significantly different. Conclusions：Ab interno circumferential trabeculotomy achieved comparable outcomes to ab externo trabeculotomy and may be an effective surgical option for patients with primary open-angle glaucoma.